A Short Communication : Monograph on Impulse Buying During the COVID-19 Pandemic - Sen, Shaon (Indian Journal of Marketing, 2022)
This article collated various findings on consumers’ impulse buying, specifically during the COVID-19 pandemic. A detailed literature review revealed interesting facts about the pre-studied antecedents of impulse buying. It is found that perceived risk, which is known to hinder consumers’ impulse buying earlier, surprisingly appeared to facilitate consumer impulse buying during the infamous global pandemic. The shift happened due to the various psychological changes that consumers experienced during the pandemic. This research monograph is interested in documenting the findings on impulse buying during the pandemic because it is essential to understand consumer changes. The post-pandemic world of consumers’ buying behavior and the pattern is likely to change. Researchers correctly pointed out to this concern that whether the changes that the pandemic has caused will sustain or not. Moreover, scholars have also estimated what changes are probable to appear in the consumers’ buying process. This study extensively puts forward the detailed findings, facilitating researchers and practitioners to devise their course of action post the COVID-19 pandemic.